Marked variation in heritability estimates of left ventricular mass depending on modality of measurement - Nethononda, R; McGurk, K; Whitworth, P; Francis, J; Mamasoula, C; Cordell, H; Neubauer, S; Keavney, B; Mayosi, B; Farrall, M; Watkins, H (Nature Research, 2019)
Left ventricular (LV) hypertrophy is a strong risk factor for heart failure and cardiovascular death. ECG measures of LV mass are estimated as heritable in twin and family-based analyses and heritability estimates of LV mass measured by echocardiography are lower. We hypothesised that CMR-derived measurements, being more precise than echocardiographic measurements, would advance our understanding of heritable LV traits. We phenotyped 116 British families (427 individuals) by CMR and ECG, and undertook heritability analyses using variance-components (QTDT) and GWAS SNP-based (GCTA-GREML) methods. ECG-based traits such as LV mass and Sokolow-Lyon duration showed substantial estimates of heritability (60%), whereas CMR-derived LV mass was only modestly heritable (20%). However, the ECG LV mass was positively correlated with the lateral diameter of the chest (rho = 0.67), and adjustment for this attenuated the heritability estimate (42%). Finally, CMR-derived right ventricular mass showed considerable heritability (44%). Heritability estimates of LV phenotypes show substantial variation depending on the modality of measurement, being greater when measured by ECG than CMR. This may reflect the differences between electrophysiological as opposed to anatomical hypertrophy. However, ECG LV hypertrophy traits are likely to be influenced by genetic association with anthropometric measures, inflating their overall measured heritability.